A case-control study identifying the frequency and spectrum of chromosomal anomalies and variants in a cohort of 1000 couples with a known history of recurrent pregnancy loss in the Eastern region of India - Abhik Chakraborty; Sujata Kar; Purna Chandra Mohapatra; Birendranath Banerjee (Wolters Kluwer Medknow Publications, 2021)
Background: Recurrent pregnancy loss (RPL) is a common occurrence that affects up to 15% of couples in their reproductive years. In both males and females with RPL and infertility, chromosomal abnormalities play a significant impact. Aim: The study was designed to examine the involvement of chromosomal anomalies and the frequency of certain chromosomal variants persistent among couples experiencing RPL. Setting and Design: This case-control study was conducted on 1000 couples from January 2015 to September 2020 in the state of Odisha, India, strictly adhering to principles of Helsinki Declaration (1975). The study was performed at the School of Biotechnology, KIIT University in collaboration with inDNA Life Sciences Private Limited. Materials and Methods: A cohort of 1148 individuals with a history of RPL were selected for the study and they were screened with respect to fertile controls for the presence of any chromosomal anomaly using G-banding, nucleolar organizing region (NOR)-banding and fluorescence in situ hybridisation wherever necessary. Statistical Analysis: The connection between distinct polymorphic variations and the occurrence of RPL was assessed using Fisher's exact test. Significant was defined as a P ≤ 0.005. Results: One hundred and thirty-four individuals were found to harbor chromosomal anomalies. This study elucidates that along with balanced chromosomal translocations, the involvement of polymorphic variants also plays a significant role in cases of RPL. Conclusion: The cumulative occurrence of chromosomal anomalies and variants across our cohort of 1148 individuals indicates that the chromosomal assessment of all couples experiencing RPL must be performed by all the clinicians. This study aids us in identifying chromosomal polymorphisms as major players of RPL in addition to novel chromosomal translocations.